Antibiotic Susceptibility Profile and Detection of Plasmid-Mediated Quinolone Resistant Genes Among Extended Spectrum β-Lactamases (ESBL) Producing Uropathogens in Women - Kaur, Rajanbir; Singh, Drishtant; Kesavan, Anup Kumar; Chauhan, Abhishek; Tuli, Hardeep Singh; Kaur, Rajinder (Scripta Medica, 2023)
Background/Aim: The most common bacterial diseases in women around the world are urinary tract infections. Aim of this study, was to evaluate the prevalence and current antibiotic resistance rate of uropathogens isolated from the female patients of a tertiary care hospital in Amritsar, Punjab, India.  Methods: Samples were collected from patients showing urinary tract infection (UTI) symptoms and analysed using microscopy, dipstick test and urine culturing followed by identification and characterisation of to identify the uropathogens. Antibiotic susceptibility test and MIC were performed.  Results: The results revealed that E coli (35.5 %) was the most prominent uropathogen followed by Klebsiella spp (21 %), Enterobacter spp (17 %), Acinetobacter (11 %), Enterococcus spp (6 %), Pseudomonas spp (4.5 %), coagulase negative Staphylococci (4 %), coagulase-positive Staphylococci (0.5 %) and Corynebacterium aurimucosum (0.5 %). The antibiotic susceptibility profile study reported eight isolates with multi-drug resistance properties. However, gentamicin, imipenem and meropenem were found to be the most effective antibiotics against the isolated uropathogens. All the extended spectrum β-lactamase (ESBL)-positive isolates possess the quinolone-resistant gene qnrB, while qnrA was absent.Conclusion: The current study revealed that for appropriate treatment, it is crucial to be aware of the epidemiological data regarding the disease and to begin any empirical antibiotic treatment.